Pengaruh Promosi dan Harga Terhadap Keputusan Pembelian Konsumen Pada Toko Dexalove Collection - Sandra Dewi Safitri; Irwan Raharja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of promotion and price on consumer purchasing decisions at Dexalove Collection Stores. To determine the number of samples in the study, researchers used the Slovin formula, where the Slovin formula was used when calculating data in the form of a survey with the population in this study taken from consumers who shopped at the Dexalove collection in April 2023 as many as 1,816 consumers. So, it can be concluded that the sample in this study was 95 respondents with a sampling technique using purposive sampling. The test methods in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, correlation determination test, f test, and t test. The results obtained in this study showed that the f test results were sig 0.000 <0.05 and the t test results were sig (0.000 <0.05). that there is an influence of promotion and price on consumer purchasing decisions at the Dexalove Collection Store where this can be proven by the results of the data quality test, namely the value of r count is greater than r table. And the correlation value in this study shows that the relationship between the effect of promotion and price on consumer purchasing decisions at the Dexalove Collection Store concludes that the results of the degree of correlation coefficient are high.